2023
DOI: 10.1007/s00402-023-04836-8
|View full text |Cite
|
Sign up to set email alerts
|

Humeral shaft fracture: systematic review of non-operative and operative treatment

Abstract: Introduction Humeral shaft fractures can be treated non-operatively or operatively. The optimal management is subject to debate. The aim was to compare non-operative and operative treatment of a humeral shaft fracture in terms of fracture healing, complications, and functional outcome. Methods Databases of Embase, Medline ALL, Web-of-Science Core Collection, and the Cochrane Central Register of Controlled Trials (CENTRAL) were systematically searched for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 179 publications
0
4
0
Order By: Relevance
“…Both DCPs and IMNs have their own sets of advantages and disadvantages. A recent systematic review conducted by Bergen et al [ 21 ] that included 173 studies on the subject concluded that plates have higher fracture healing rates and the least complications if radial nerve palsies are excluded. On the contrary, a study that also took into consideration operative measurements such as surgical time and intraoperative blood loss concluded that both techniques can produce similar results, although IMN was a less invasive procedure [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both DCPs and IMNs have their own sets of advantages and disadvantages. A recent systematic review conducted by Bergen et al [ 21 ] that included 173 studies on the subject concluded that plates have higher fracture healing rates and the least complications if radial nerve palsies are excluded. On the contrary, a study that also took into consideration operative measurements such as surgical time and intraoperative blood loss concluded that both techniques can produce similar results, although IMN was a less invasive procedure [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the majority of the trials was started after 2010, indicating the novelty of this topic. Management of PHF was originally mostly conservative [ 38 ]. However, as years passed, integrating operative management for patients with displaced fractures showed good clinical and functional outcomes [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Humeral shaft fractures account for about 3% of all orthopedic injuries ( 2 ). Radial nerve palsy (RNP) is a common complication of humeral shaft fractures and is classified into primary RNP and secondary RNP ( 3 ). Primary RNP refers to nerve injuries potentially induced by localized compression at the fracture site, transverse disruption of fracture fragments, or local swelling at the moment of the fracture ( 4 ).…”
Section: Introductionmentioning
confidence: 99%